2016
DOI: 10.3892/mmr.2016.5601
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin attenuates cyclosporine A-induced renal fibrosis by inhibiting hypermethylation of the klotho promoter

Abstract: Chronic kidney disease is increasingly considered to be a worldwide public health problem and usually leads to renal fibrosis. In the present study, curcumin, a polyphenol pigment extracted from turmeric, was demonstrated to exert protective effects on renal fibrosis via the suppression of transforming growth factor‑β (TGF‑β) downstream signaling, such as plasminogen activator inhibitor‑1 (PAI‑1), α‑smooth muscle actin (α‑SMA) and collagen I (Col I) downregulation. The present findings demonstrate that curcumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 35 publications
0
27
0
Order By: Relevance
“…The decrease in Klotho transcription in kidney disease has been attributed to regulation by NF-κB or Angiotensin II or more recently to modifications of Klotho promoter acetylation 23 or methylation. [62][63][64] We observed an induction of ATF3 by proteinuria in different models, both in proximal and distal tubular segments. Recently, it was demonstrated by chromatin immunoprecipitation that ATF3 binds to the Klotho promoter as a heterodimer with c-Jun.…”
Section: Discussionmentioning
confidence: 80%
“…The decrease in Klotho transcription in kidney disease has been attributed to regulation by NF-κB or Angiotensin II or more recently to modifications of Klotho promoter acetylation 23 or methylation. [62][63][64] We observed an induction of ATF3 by proteinuria in different models, both in proximal and distal tubular segments. Recently, it was demonstrated by chromatin immunoprecipitation that ATF3 binds to the Klotho promoter as a heterodimer with c-Jun.…”
Section: Discussionmentioning
confidence: 80%
“…Tirkey et al (42) reported that, through its antioxidant activity, Cur effectively salvaged CsA-induced nephrotoxicity. Furthermore, Hu et al (43) demonstrated that the protective effect of Cur may be mediated by inhibiting the hypermethylation of the klotho promoter. The present study confirmed that Cur significantly increased renal antioxidant capacity and decreased the Bax/Bcl-2 ratio in CsA-treated HK-2 cells, which may be associated with the improvements in CsA-induced renal failure and renal tubular deformation and cell vacuolization following Cur treatment in rats.…”
Section: Discussionmentioning
confidence: 99%
“…Curcumin (diferuloylmethane) has been reported to exhibit several beneficial properties, including anti-inflammatory, anti-oxidative, anti-proliferative, and anti-apoptotic activities ( 6 ). Accumulating evidence has demonstrated preventive effects of curcumin in fibrotic diseases, including oral submucosal ( 7 ), liver ( 8 ), lung ( 9 ), and kidney fibrosis ( 10 ). In a previous study, the cardiac protective effect of curcumin was demonstrated in several heart diseases, such as hypertension, myocardial infarction, and diabetic cardiomyopathy ( 11 13 ).…”
Section: Introductionmentioning
confidence: 99%